Application of Islamic Communication Principles on Santri's Moral Development Nurul Azhar Islamic Boarding School Talawe Village, Kab. Sidrap - Fikruzzaman, Fikruzzaman; Arsyad , Abd. Rahim (IAIN Parepare, 2021)
This study discusses the application of Islamic communication principles in fostering students of Nurul Azhar Talawe with the problems 1) How are the morals of the students of the Nurul Azhar Talawe Sidrap Islamic boarding school, 2) What are the forms and methods of communication in fostering the morals of students, and 3) How is the application of Islamic communication principles in fostering the character of the students of the Nurul Azhar Talawe Islamic boarding school. This study is a qualitative field research. Data collection is carried out using three methods: observation, interviews and documentation. Data collection instruments: observation sheets, interview instruments and list of documents. The data processing and analysis technique used a data validity test using source triagulation. The results showed that; 1) The morals of the Nurul Azhar Islamic boarding school students at the beginning of their entry still had bad behavior, and most of them behaved well, 2) The form of communication for the boarding school supervisor was interpersonal communication and group communication by means of communication, among others; qawlan layyina with gentle, soothing words, qawlan maisura always says gentle, polite, and polite, Qawlan Ma'rufan always talks about useful things, 3) The application of Islamic communication principles with a sincere attitude Teaching to become a santri has the character of Honest, love cleanliness, always say positive, only words and deeds, listen more than talk, always realize that all human behavior cannot be separated from the supervision of Allah Swt.